Employment research and state traditions: a comparative history of Britain, Germany, and the United States - Frege, Carola M. (New York, 2007)
"Contemporary employment research tackles an increasingly globalised subject, much of it using empiricist and a-theoretical methods increasingly embedded in a market-economic paradigm. However, this stands in stark contrast to employment research's historical roots. Exploring these roots, Carola Frege traces how employment research was born out of the industrial and also democratic transformations of the 19th century and shows that the variations of employment research can be traced back to nation-specific state traditions. In particular, how countries conceptualised their relationship between political and industrial democracy, to what extent their labour movements were more state-oriented, and what influence the state had on the organisation of higher education and scientific research, and shaped research topics, methods, theories, and paradigms. The book argues that these different research cultures are still with us today, despite increasing globalisation of the subject matter and growing internationalisation of the academic world. Based on a comparative historical analysis of research characteristics in Britain, Germany, and the US, this book investigates how employment research developed in different ways in different countries. A longitudinal cross-country comparison of publications in the main journals of the field reveals that employment research is still deeply embedded in longstanding country-specific institutional and ideational traditions. Carola Frege makes the case for embracing this diversity, and rejuvenating the subject of employment research through a rediscovery of its policy-oriented research traditions, and a reinstatement of its relevance for society."